Taxonomic and nomenclatural status of the Mexican species in the Tillandsia viridiflora complex (Bromeliaceae) - Krömer, Thorsten; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Ehlers, Renate; Lautner, Jürgen (Instituto de Ecología, A.C., 2012)
Based on a systematic study of the Mexican species in the Tillandsia viridiflora complex, the taxonomic and nomenclatural status of these species is clarified. The former synonym T. macropetala is reestablished as a species. An identification key for the complex species (T. grandis, T. macropetala and T. viridiflora), as well as a complete synonymy and detailed descriptions of the taxa are included.